If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -3x + 18 Reorder the terms: y = 18 + -3x Solving y = 18 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 18 + -3x
| 28=4y-6 | | 2m+7=22 | | (6x-2)=56 | | A-3.5=14 | | 5x^2+17x+-12=0 | | e^6x=13 | | 9(-4x+2)=7x | | 2x+30=-2x+2 | | 5x+3y=-29 | | e^3x=13 | | 6x^2+11x+-2=0 | | 5-(-7)=12 | | 5(w+12)= | | 4x-5+3x=9 | | 4q=7q+37 | | 1.5-0.25(a+4)=3+(.05-0.5a) | | 4t^2+18t-400=0 | | -20=-7x+1 | | 5(-4x-3)=13x+9 | | -50-7x=-3x+62 | | 312x+51=33 | | 4c-7=3c | | 9x+10y=-16 | | 9y-15=-2(y-6) | | 34+5n=9 | | 20-2n=80 | | 3d-4(5d-8)=-12-6d | | 2x+(2x-1)=31 | | 5x+7+3x=-1 | | 8(x+2)=-6(x+5) | | (2x+9)(4x+2)= | | 15m+3m=-18 |